Structural basis for 5'-ETS recognition by Utp4 at the early stages of ribosome biogenesis - Calviño, Fabiola R.; Kornprobst, Markus; Schermann, Géza; Birkle, Fabienne; Wild, Klemens; Fischer, Tamás; Hurt, Ed; Ahmed, Yasar Luqman; Sinning, Irmgard (PLOS ONE, 2017)
Eukaryotic ribosome biogenesis begins with the co-transcriptional assembly of the 90S pre-ribosome. The ‘U three protein’ (UTP) complexes and snoRNP particles arrange around the nascent pre-ribosomal RNA chaperoning its folding and further maturation. The earliest event in this hierarchical process is the binding of the UTP-A complex to the 5'-end of the pre-ribosomal RNA (5'-ETS). This oligomeric complex predominantly consists of β-propeller and α-solenoidal proteins. Here we present the structure of the Utp4 subunit from the thermophilic fungus Chaetomium thermophilum at 2.15 Å resolution and analyze its function by UV RNA-crosslinking (CRAC) and in context of a recent cryo-EM structure of the 90S pre-ribosome. Utp4 consists of two orthogonal and highly basic β-propellers that perfectly fit the EM-data. The Utp4 structure highlights an unusual Velcro-closure of its C-terminal β-propeller as relevant for protein integrity and potentially Utp8 recognition in the context of the pre-ribosome. We provide a first model of the 5'-ETS RNA from the internally hidden 5'-end up to the region that hybridizes to the 3'-hinge sequence of U3 snoRNA and validate a specific Utp4/5'-ETS interaction by CRAC analysis.
Gesehen am 11.04.2018